Derotational Osteotomy and Plate Fixation of the Radius and Ulna for the Treatment of Congenital Proximal Radioulnar Synostosis - Hamiti, Yimurang; Yushan, Maimaiaili; Yalikun, Ainizier; Lu, Cheng; Yusufu, Aihemaitijiang (Frontiers in Surgery, 2022)
Purpose To evaluate clinical outcomes of derotational osteotomy followed by plate fixation at radius and ulna for the treatment of congenital proximal radioulnar synostosis. Methods A total of 10 eligible patients (12 forearms) with congenital proximal radioulnar synostosis were admitted to our institution from January 2013 to January 2016 and treated by radioulnar derotational osteotomy followed by plate fixation. There were 5 males and 5 females with an average age of 5.4 ± 2.0 (3 to 9) years old. The average forearm position was 56.67 ± 14.36 ° (range, 40° to 80° ) pronation before surgery. According to the classification system of Cleary and Omer, 4 forearms were categorized as type II, 7 were type III, and 2 were type IV. The pre- and postoperative forearm function was recorded and evaluated by the Failla scoring system. Results All included patients were successfully followed up in an average time of 73.90 ± 8.24 months (range, 61 to 84 months). The mean correction of the forearm achieved was 53.33° ± 12.67° (range, 35° to 70°). An average final position was 3.33° ± 14.98° pronation (range, 20° of supination to 25° of pronation). Bony union was achieved in a mean of 10.38 ± 1.25 weeks (range, 8.4 to 12.3 weeks) with no loss of correction. There were no incidences of nonunion, osteomyelitis, neurologic or circulatory complications. The functional results were good in 1 forearm, fair in 8 and poor in 3 preoperatively. In terms of final follow-up function evaluations, 3 forearms excellent, 6 forearms good, and 3 forearms fair. Conclusions Congenital proximal radioulnar synostosis can be successfully treated using Derotational osteotomy and plate fixation of the radius and ulna, which is an effective method with fewer postoperative complications and expected clinical outcomes.